2021
DOI: 10.1002/jsfa.11098
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide in non‐centrifugal sugars and syrups

Abstract: BACKGROUND Acrylamide in foods has been widely studied because of its possible carcinogenicity. Most of the foods investigated were prepared using low moisture and high temperature conditions. Non‐centrifugal sugars (NCSs), which have been promoted as ‘non‐chemical’ natural sweeteners, contain precursors of acrylamide and their production processes involved prolonged heating. The acrylamide content in 32 commercial NCSs from coconut, cane and palmyra palm purchased in Asian countries was investigated. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The high temperature of roasting peanuts and heating jaggery could contribute to the high acrylamide levels in Peanut Balls. On the other hand, Phaeon et al ( 34 ) recently reported that a maximum amount of acrylamide (4,011 ng/g) was found in jaggery. Moreover, the main amino acid present in jaggery is asparagine, which reacts with reducing sugars to form acrylamide ( 34 ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The high temperature of roasting peanuts and heating jaggery could contribute to the high acrylamide levels in Peanut Balls. On the other hand, Phaeon et al ( 34 ) recently reported that a maximum amount of acrylamide (4,011 ng/g) was found in jaggery. Moreover, the main amino acid present in jaggery is asparagine, which reacts with reducing sugars to form acrylamide ( 34 ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Phaeon et al ( 34 ) recently reported that a maximum amount of acrylamide (4,011 ng/g) was found in jaggery. Moreover, the main amino acid present in jaggery is asparagine, which reacts with reducing sugars to form acrylamide ( 34 ). The main carbohydrate in jaggery is sucrose ( 35 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations